1985
DOI: 10.1152/jappl.1985.59.2.634
|View full text |Cite
|
Sign up to set email alerts
|

Heat transfer pathways between fetal lamb and ewe

Abstract: Heat produced by the fetus exists to the mother by one of two principal routes: by fetal-maternal exchange in the placenta or through the fetal skin to the amniotic fluid and uterine wall. We measured heat conductances along each pathway to estimate the fraction of total heat exiting each route. Thermistors were placed in the fetal aorta, two different sites in the amniotic fluid, and in a maternal artery. Five days after surgery we injected a total of 280 ml of ice-cold saline into the two separate amniotic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
1

Year Published

1991
1991
2012
2012

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 0 publications
0
38
1
Order By: Relevance
“…One possibility is that the carotid rete, which in the sheep helps cool the brain after birth (1), might remove heat from arterial blood supplying the brain. This seems unlikely, however, because before birth there is no effective sink into which heat might be deposited; the amniotic fluid is only 0.1-0.2°C cooler than fetal core temperature, and thus the temperature gradient for heat flux from the rete is small (18). Alternatively, a larger fraction of carotid flow perfusing non-brain tissues such as the face and scalp might be diverted to the brain during severe hypoxia than was evident from carotid blood flow measurements.…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that the carotid rete, which in the sheep helps cool the brain after birth (1), might remove heat from arterial blood supplying the brain. This seems unlikely, however, because before birth there is no effective sink into which heat might be deposited; the amniotic fluid is only 0.1-0.2°C cooler than fetal core temperature, and thus the temperature gradient for heat flux from the rete is small (18). Alternatively, a larger fraction of carotid flow perfusing non-brain tissues such as the face and scalp might be diverted to the brain during severe hypoxia than was evident from carotid blood flow measurements.…”
Section: Discussionmentioning
confidence: 99%
“…However, these results suggest that body temperature measurement is useful for predicting impending parturition in this species. In vivo studies [13] and model predictions [14] have indicated that fetal lambs lose 80 to 85% of their heat via transfer to the placenta and the other 15 to 20% via transfer through the uterine wall. Blood flow to the placenta, was directly affected by maternal temperature, and this effect would influence heat dissipation by the fetus [14].…”
Section: Discussionmentioning
confidence: 99%
“…The contribution of the placental heat production to the fetal-maternal temperature difference has been estimated to be 0-07°C (Schr6der, Gilbert & Power, 1988). Estimates of both conductances have been obtained in fetal sheep (Gilbert, Schroder, Kawamura, Dale & Power, 1985) by observing fetal and amniotic fluid temperatures after injection of cold saline into the amniotic cavity. On (Schroder et al 1988) that changes of fetal heat production (oxygen consumption) and cardiac output (umbilical blood flow) will indeed influence fetal temperature, but the effects of fetal thermoregulatory efforts are very limited.…”
Section: Placental Heat Exchangementioning
confidence: 99%